Method for producing sulfide solid electrolyte

By mixing elemental sulfur and lithium sulfide in the solvent, and using a solvent of an ether solvent and an alcohol solvent through heating reaction, the problems of low manufacturing efficiency and difficulty in improving the purity of sulfide solid electrolyte in the prior art are solved, and high ionization is achieved Conductivity and efficient production.

CN119487587APending Publication Date: 2025-02-18IDEMITSU KOSAN CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380050905.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-09
Filing Date
2023-07-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, when manufacturing sulfide solid electrolytes with high ionic conductivity, the reaction time is long, the production efficiency is low, and the purity and ionic conductivity are difficult to improve.

Method used

The primary sulfur and lithium sulfide are mixed in a solvent as raw materials, and reacted by heating to form a sulfide solid electrolyte with high ionic conductivity. Use an organic solvent of an ether solvent and an alcohol solvent as a solvent to ensure that the total amount of the solvent contains more than 60% of the ether solvent and alcohol solvent to promote the formation of free radicals and anions of sulfur and improve the formation efficiency of electrolyte precursors.

Benefits of technology

It has achieved the improvement of the ionic conductivity of the sulfide solid electrolyte in a very short time, the purity and production efficiency of the electrolyte are improved, and is suitable for various types of sulfide solid electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217662720000321
    Figure BDA0005217662720000321
  • Figure HDA0005217662750000011
    Figure HDA0005217662750000011
  • Figure HDA0005217662750000012
    Figure HDA0005217662750000012
Patent Text Reader

Abstract

A method for producing a sulfide solid electrolyte, comprising: mixing, in a solvent, raw material-containing substances including a plurality of raw materials including at least one type of atom selected from among a lithium atom, a phosphorus atom, a sulfur atom, and a halogen atom; the solvent is an organic solvent containing an ether solvent and an alcohol solvent in an amount of 60% by volume or more based on the total amount of the solvent, and the starting material-containing substance contains elemental sulfur and lithium sulfide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a sulfide solid electrolyte. Background Art

[0002] In recent years, with the rapid popularization of information-related devices or communication devices such as personal computers, cameras and mobile phones, the development of batteries used as their power sources has also received attention. In the past, in batteries used for such purposes, electrolytes containing flammable organic solvents were used, but by making the battery fully solid, the safety device is simplified because no flammable organic solvent is used in the battery, and the manufacturing cost and productivity are excellent. Therefore, the development of batteries in which the electrolyte is replaced by a solid electrolyte layer is carried out.

[0003] As a method for manufacturing a solid electrolyte for a solid electrolyte layer, it is roughly divided into a solid phase method and a liquid phase method, and the liquid phase method includes a uniform method in which a solid electrolyte material is completely dissolved in a solvent, and an inhomogeneous method in which a solid electrolyte material is not completely dissolved but a suspension coexists with solid and liquid. For example, as a uniform method in the liquid phase method, a method of dissolving a solid electrolyte in a solvent to reprecipitate it is known (for example, refer to patent document 1), and as an inhomogeneous method, a method of reacting solid electrolyte raw materials such as lithium sulfide in a solvent containing a polar aprotic solvent is known (for example, refer to patent documents 2 and 3), and a method for manufacturing a solid electrolyte using a specific compound having an amino group as a complexing agent (for example, refer to patent documents 4 and 5). Non-patent document 1 records: using tetrahydrofuran and ethanol, a tetrahydrofuran-ethanol precursor solution of Li6PS5Br is prepared, which is dried and heated to produce a solid electrolyte having a argyrodite-type crystal structure and the argyrodite-type crystal structure having a composition of Li6PS5Br.

[0004] In addition, non-patent documents 2 and 3 describe that Li2S, P2S5 and S (7:3:x (x=3, 5 and 7) molar ratio) are added to a mixed solvent (1:1:0.05 (volume ratio)) of acetonitrile, tetrahydrofuran and ethanol to generate lithium polysulfide and highly reactive sulfur radicals, and after stirring for several minutes, the mixture is dried under vacuum and heated at a heating temperature of 270°C, 350°C, etc. to produce Li7P3S 11 A crystalline solid electrolyte with a composition of

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-191899

[0008] Patent Document 2: International Publication No. 2014 / 192309

[0009] Patent Document 3: International Publication No. 2018 / 054709

[0010] Patent Document 4: International Publication No. 2020 / 105737

[0011] Patent Document 5: International Publication No. 2021 / 230189

[0012] Non-patent literature

[0013] Non-patent document 1: J. Mater. Chem. A, 2019, 7, 558-566

[0014] Non-patent document 2: 62nd Battery Symposium Draft Paper, published on November 29, 2021, All-solid-state batteries / sulfide electrolytes, 3E01

[0015] Non-patent literature 3: Adv. Energy Sustainability Res., 2022, 3, 2200019 Summary of the invention

[0016] Technical problem to be solved by the invention

[0017] The present invention has been made in view of the above circumstances, and an object of the present invention is to efficiently provide a sulfide solid electrolyte having improved ion conductivity.

[0018] Solutions for solving the above technical problems

[0019] The method for producing the sulfide solid electrolyte of the present invention is:

[0020] A method for manufacturing a sulfide solid electrolyte, comprising:

[0021] mixing a raw material containing a plurality of raw materials in a solvent, wherein the raw materials contain at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms; and

[0022] Then heating,

[0023] The solvent comprises an organic solvent of an ether solvent and an alcohol solvent in an amount of 60% by volume or more based on the total amount of the solvent.

[0024] The raw material contains elemental sulfur and lithium sulfide.

[0025] Effects of the Invention

[0026] According to the present invention, a sulfide solid electrolyte having improved ion conductivity can be provided efficiently. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the X-ray diffraction spectrum of the powder obtained in Example 1.

[0028] Figure 2 These are the X-ray diffraction spectra of the powders obtained in Examples 2 to 7.

[0029] Figure 3 These are the X-ray diffraction spectra of the powders obtained in Examples 2 to 7.

[0030] Figure 4 This is the X-ray diffraction spectrum of the powder obtained in Example 10.

[0031] Figure 5 This is the X-ray diffraction spectrum of the powder obtained in Comparative Example 1.

[0032] Figure 6 This is the X-ray diffraction spectrum of the powders obtained in Examples 8 and 9.

[0033] Figure 7 This is the X-ray diffraction spectrum of the powders obtained in Examples 8 and 9. DETAILED DESCRIPTION

[0034] Hereinafter, an embodiment of the present invention (hereinafter sometimes referred to as "the present embodiment") is described. In addition, in this specification, the upper and lower limit values ​​involved in the numerical ranges of "above", "below", and "to" are values ​​that can be arbitrarily combined, and the values ​​of the embodiments can also be used as the upper and lower limit values. In addition, preferred provisions can be adopted arbitrarily. That is, a preferred provision can be combined with another preferred provision or multiple provisions. It can be said that the combination of preferred provisions is more preferred.

[0035] (Discovery made by the present inventors to complete the present invention)

[0036] The present inventors have conducted intensive studies to solve the above-mentioned technical problems, and as a result, have found the following matters, thereby completing the present invention.

[0037] In recent years, with the goal of practical application of all-solid-state batteries, the liquid phase method has attracted attention as a method that can be synthesized simply and in large quantities in addition to versatility and applicability. As a solid phase method, a method represented by a mechanical grinding method can be cited, in which a solid electrolyte raw material is crushed and mixed with a pulverizer and reacted to obtain a solid electrolyte, but due to the high cost of equipment and the need for a large amount of initial investment, it is difficult to reduce costs.

[0038] On the other hand, regarding the liquid phase method, for example, in the method described in Patent Document 1, Li2S and P2S5 (80:20) are subjected to mechanical grinding for 20 hours, dissolved in N-methylformamide (NMF), and dried to obtain a solid electrolyte, which requires 20 hours of mechanical grinding. In the method described in Patent Document 2, Li2S and P2S5 are contacted for 24 hours in a mixed solvent of a hydrocarbon solvent (toluene) and a polar aprotic solvent (tetrahydrofuran) to react, and in the method described in Patent Document 3, when Li3PS4·DME (electrolyte precursor; complex) is produced in dimethoxyethane (DME), stirring is performed for about 10 days. In addition, in the method using a complexing agent described in Patent Documents 4 and 5, the reaction is carried out by stirring the solid electrolyte raw material and the complexing agent together for 12 to 72 hours, and further for more than 72 hours. In addition, in the method described in Non-Patent Document 1, the reaction is also carried out overnight, that is, the reaction is carried out for about 12 hours. As described above, since the reaction time is long in the conventional production method, better production efficiency is required.

[0039] In addition, in the method described in non-patent document 1, drying is performed for 3 hours to remove tetrahydrofuran and ethanol. However, oxides as impurities are sometimes generated due to the reaction of a portion of the residual ethanol with the solid electrolyte. A portion of Li2S, which is commonly used as a raw material for solid electrolytes, reacts with alcohol solvents such as ethanol to generate alcohol lithium such as lithium ethanol, which does not contribute to the reaction with raw materials such as phosphorus sulfide (e.g., phosphorus pentasulfide (P2S5)) commonly used with Li2S. Therefore, there is a situation where the purity of the sulfide solid electrolyte is reduced and the ion conductivity is reduced, and quality improvement is also required.

[0040] In the methods described in Non-Patent Documents 2 and 3, a crystalline sulfide solid electrolyte is obtained by stirring for several minutes, drying for one hour, and heating for one hour, which can be said to have excellent production efficiency. 11 Therefore, it is not clear whether it can be applied to other solid electrolytes, such as solid electrolytes containing halogen atoms. Moreover, in these non-patent documents, it is recorded that ethanol acts on lithium of lithium polysulfide to generate highly reactive sulfur radicals. Therefore, it is also conceivable that if lithium halide containing Li like Li2S is used as a raw material, the generation mechanism of sulfur radicals is hindered and an efficient reaction cannot be performed.

[0041] Thus, the prior art has both advantages and disadvantages, and there is room for improvement in producing sulfide solid electrolytes with high ionic conductivity at higher production efficiency.

[0042] Therefore, the present inventors focused on elemental sulfur as a raw material and studied the use of a raw material containing halogen atoms in order to improve ion conductivity using elemental sulfur as a raw material, and found that a sulfide solid electrolyte with improved ion conductivity can be obtained in a very short time.

[0043] (Various Aspects of the Present Embodiment)

[0044] The method for producing a sulfide solid electrolyte according to the first aspect of the present embodiment is as follows:

[0045] A method for manufacturing a sulfide solid electrolyte, comprising:

[0046] mixing a raw material containing a plurality of raw materials in a solvent, wherein the raw materials contain at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms; and

[0047] Then heating,

[0048] The solvent comprises an organic solvent of an ether solvent and an alcohol solvent in an amount of 60% by volume or more based on the total amount of the solvent.

[0049] The raw material contains elemental sulfur and lithium sulfide.

[0050] In the method for producing a sulfide solid electrolyte of the present embodiment, it is necessary to use elemental sulfur and lithium sulfide in combination as raw materials. It is considered that elemental sulfur reacts with lithium sulfide in a solvent to become a polysulfide of lithium and generates sulfur free radicals. Sulfur free radicals are highly reactive and promote reactions with other raw materials such as phosphorus pentasulfide and other raw materials containing halogen atoms to generate soluble polysulfides (hereinafter also referred to as "polysulfides") which are precursors of sulfide solid electrolytes (hereinafter also referred to as "electrolyte precursors"). It is considered that by decomposing the polysulfide by heating or the like, a sulfide solid electrolyte with improved ion conductivity can be efficiently produced. In addition, the inventors of the present invention conducted further research and found that, in addition to sulfur free radicals, for example, S4 2- Sulfur active species such as sulfur anions also contribute to the formation of electrolyte precursors (polysulfides) by promoting reactions with other raw materials, and it is important to generate these sulfur active species in a well-balanced manner.

[0051] In addition, in the manufacturing method of the present embodiment, it is necessary to use an organic solvent such as an ether solvent and an alcohol solvent as a solvent, and the amount of the organic solvent used needs to be 60% by volume or more based on the total amount of the solvent. As a solvent, by using a solvent containing at least an organic solvent having oxygen atoms such as an ether solvent and an alcohol solvent in a content of more than a specified amount, sulfur active species such as sulfur radicals and anions suitable for the formation of an electrolyte precursor are generated in a well-balanced manner, thereby promoting the reaction with other raw materials, resulting in the ability to efficiently manufacture a sulfide solid electrolyte with improved ion conductivity. In this regard, for example, in the methods described in the above-mentioned non-patent documents 2 and 3, an ether solvent (tetrahydrofuran) and a nitrile solvent (acetonitrile) are used in the same amount (41.7 to 49.8% by volume, respectively), and the total amount of the ether solvent and the alcohol solvent used is about 50.2 to 58.3% by volume. It can be considered that sulfur active species such as sulfur radicals and anions suitable for the formation of an electrolyte precursor are not generated in a well-balanced manner. Therefore, as described above, it is limited to Li7P3S 11 The invention relates to a crystalline solid electrolyte having a composition of , and its application to other solid electrolytes such as a sulfide solid electrolyte containing halogen atoms is not yet clear.

[0052] According to the production method of this embodiment, by using a raw material containing multiple raw materials containing at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms, and containing elemental sulfur and lithium sulfide, and by mixing these raw material contents in a specific solvent, the generation of active sulfur species such as sulfur radicals suitable for the formation of an electrolyte precursor can be promoted in a well-balanced manner, and the generation of polysulfides that serve as precursors of a sulfide solid electrolyte can be promoted, resulting in the efficient production of a sulfide solid electrolyte with improved ion conductivity.

[0053] By mixing the above-mentioned raw material contents, a precursor of a sulfide solid electrolyte, an amorphous sulfide solid electrolyte, and a crystalline sulfide solid electrolyte that are further heated can be mainly generated. By mixing, a soluble polysulfide is generated as an electrolyte precursor, and by heating, the polysulfide is decomposed to become an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte, and the crystallinity of the crystalline sulfide solid electrolyte is improved. In addition, the solvent is also removed. Therefore, in the manufacturing method of this embodiment, it can be said that heating is mainly performed for the decomposition of polysulfides, the removal of solvents and crystallization. In addition, the removal of elemental sulfur generated by the decomposition of polysulfides can also be performed by evaporation achieved by heating, but this can also be applied to methods other than heating such as solvent washing and hydrodesulfurization.

[0054] A method for producing a sulfide solid electrolyte according to a second aspect of the present embodiment is, in the above-mentioned first aspect,

[0055] The solvent is an ether solvent and an alcohol solvent.

[0056] By using ether solvents and alcohol solvents as solvents, the generation of sulfur active species such as sulfur radicals suitable for the formation of electrolyte precursors can be carried out in a well-balanced manner, the reaction of the raw materials is promoted, and the formation of the electrolyte precursor (polysulfide) is further promoted, so that a sulfide solid electrolyte with improved ion conductivity can be produced more efficiently.

[0057] A method for producing a sulfide solid electrolyte according to a third aspect of the present embodiment is, in the first or second aspect,

[0058] The solvent includes an alcohol solvent, and the amount of the alcohol solvent used is 0.030 mol or more and 5.0 mol or less relative to 1.0 mol of the lithium sulfide.

[0059] A fourth aspect of the method for producing a sulfide solid electrolyte is, in any one of the first to third aspects,

[0060] The solvent includes an ether solvent, and the content of the ether solvent based on the total amount of the solvent is 50.0 volume % or more.

[0061] When an alcohol solvent is used, by setting its usage amount within the above range, and when an ether solvent is used, by setting its usage amount within the above range, the generation of sulfur active species such as sulfur radicals suitable for the formation of an electrolyte precursor is carried out in a well-balanced manner, the reaction of the raw materials is promoted, and the formation of the electrolyte precursor (polysulfide) is further promoted, so that a sulfide solid electrolyte with improved ion conductivity can be manufactured more efficiently.

[0062] A fifth aspect of the present embodiment provides a method for producing a sulfide solid electrolyte, in any one of the first to fourth aspects,

[0063] The halogen atom is at least one atom selected from a chlorine atom, a bromine atom, and an iodine atom.

[0064] If the sulfide solid electrolyte contains halogen atoms, it has high ion conductivity. Among them, by containing any of chlorine atoms, bromine atoms, and iodine atoms, it is easy to form an argyrodite-type crystal structure and a sulfide crystal lithium superion conductor region type II crystal structure that show particularly high ion conductivity.

[0065] A sixth method for producing a sulfide solid electrolyte according to the present embodiment is, in the first to fifth methods described above,

[0066] The heating is performed at a heating temperature of 20° C. to 500° C.

[0067] As described above, in the manufacturing method of this embodiment, heating is mainly performed for decomposition of the electrolyte precursor (polysulfide), removal of the solvent and crystallization. If the heating temperature during heating is within the above range, crystallization can be performed while removing the solvent more efficiently and reliably.

[0068] A seventh aspect of the present embodiment provides a method for producing a sulfide solid electrolyte, in the sixth aspect,

[0069] The heating is performed at a temperature of 20°C to 300°C.

[0070] The method for producing a sulfide solid electrolyte according to an eighth aspect is, in the seventh aspect,

[0071] The heating is performed by first heating at a heating temperature of 20° C. or higher and lower than 150° C. and second heating at a heating temperature of 150° C. or higher and 300° C. or lower.

[0072] During crystallization, the heating temperature can vary depending on the type of sulfide solid electrolyte to be obtained, so it cannot be generalized, but by setting it to 20°C to 300°C, a sulfide solid electrolyte having a sulfide crystallized lithium superion conductor region type II crystal structure can be efficiently manufactured.

[0073] As described above, in the manufacturing method of this embodiment, heating is mainly performed for decomposition of the electrolyte precursor (polysulfide), removal of the solvent and crystallization. If the heating temperature during heating is within the above range, crystallization can be performed while removing the solvent more efficiently and reliably.

[0074] In addition, by performing heating in multiple stages such as the first heating and the second heating, decomposition of polysulfides, removal of solvents and crystallization can be performed more efficiently. Furthermore, by performing heating, elemental sulfur generated by decomposition of polysulfides can also be removed. Removal of elemental sulfur is not limited to heating, and can also be performed by other methods such as solvent washing and hydrodesulfurization.

[0075] A ninth aspect of the present embodiment provides a method for producing a sulfide solid electrolyte, in the sixth aspect,

[0076] The heating is performed at a temperature of 200° C. to 500° C.,

[0077] A method for producing a sulfide solid electrolyte according to a tenth aspect of the present embodiment is, in the ninth aspect,

[0078] The heating is performed by heating at a heating temperature of 200° C. or higher and lower than 350° C. or heating at a heating temperature of 350° C. or higher and 500° C. or lower.

[0079] By performing the heating at a heating temperature of 200° C. to 500° C., a sulfide solid electrolyte having an argyrodite type crystal structure can be efficiently produced. The heating in multiple stages is the same as in the method for producing a sulfide solid electrolyte of the tenth aspect.

[0080] The eleventh method for producing a sulfide solid electrolyte according to the present embodiment is, in the first to tenth methods described above,

[0081] A crystalline sulfide solid electrolyte having an argyrodite-type crystal structure or a sulfide crystalline lithium superion conductor region-type II crystal structure is produced.

[0082] In the manufacturing method of the present embodiment, a desired sulfide solid electrolyte can be manufactured by changing the type and blending ratio of the solid electrolyte raw material contained in the raw material content. Crystalline sulfide solid electrolytes having an argyrodite-type crystal structure and crystalline sulfide solid electrolytes having a sulfide crystalline lithium superion conductor region II-type crystal structure are known to be sulfide solid electrolytes having extremely high ion conductivity, and are preferred as the sulfide solid electrolytes intended to be obtained by the manufacturing method of the present embodiment.

[0083] (Sulfide solid electrolyte)

[0084] In this specification, "solid electrolyte" refers to an electrolyte that remains solid at 25° C. in a nitrogen atmosphere. The sulfide solid electrolyte in this embodiment is a solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and having ion conductivity due to lithium atoms.

[0085] The “sulfide solid electrolyte” includes both an amorphous sulfide solid electrolyte and a crystalline sulfide solid electrolyte.

[0086] In this specification, the crystalline sulfide solid electrolyte refers to a sulfide solid electrolyte in which a peak derived from a solid electrolyte is observed in an X-ray diffraction pattern in an X-ray diffraction measurement, and is a material that is independent of the presence or absence of a peak derived from a raw material of the sulfide solid electrolyte. That is, the crystalline sulfide solid electrolyte includes a crystal structure derived from a solid electrolyte, and a part of it may be a crystal structure derived from the solid electrolyte, or all of it may be a crystal structure derived from the solid electrolyte. Furthermore, as long as the crystalline sulfide solid electrolyte has the above-mentioned X-ray diffraction pattern, a part of it may also include an amorphous sulfide solid electrolyte. Therefore, the crystalline sulfide solid electrolyte includes so-called glass ceramics obtained by heating an amorphous sulfide solid electrolyte to a crystallization temperature or higher.

[0087] In this specification, an amorphous sulfide solid electrolyte means an X-ray diffraction pattern having a halo pattern in which substantially no peaks other than peaks derived from the material are observed in X-ray diffraction measurement, regardless of the presence or absence of peaks derived from the raw material of the sulfide solid electrolyte.

[0088] [Method for producing sulfide solid electrolyte]

[0089] The method for producing the sulfide solid electrolyte of the present embodiment is as follows:

[0090] A method for manufacturing a sulfide solid electrolyte, comprising:

[0091] mixing a raw material containing a plurality of raw materials in a solvent, wherein the raw materials contain at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms; and

[0092] Then heating,

[0093] The solvent comprises an organic solvent of an ether solvent and an alcohol solvent in an amount of 60% by volume or more based on the total amount of the solvent.

[0094] The raw material contains elemental sulfur and lithium sulfide.

[0095] 〔Contents of mixed raw materials〕

[0096] The production method of this embodiment includes mixing a raw material-containing material including a plurality of raw materials including at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms in a solvent.

[0097] First, the production method of this embodiment will be described starting from the raw material contents.

[0098] (Ingredients contained in raw materials)

[0099] The raw material content used in this embodiment is a content containing multiple raw materials containing at least one atom selected from lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, and contains elemental sulfur and lithium sulfide. That is, the raw material content is a content containing at least elemental sulfur and lithium sulfide, and further contains multiple raw materials containing at least one atom selected from lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms.

[0100] Representative examples of the raw materials included in the raw material content include: lithium sulfide; lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); various phosphorus fluorides (PF3, PF5), various phosphorus chlorides (PCl3, PCl5, P2Cl4), various phosphorus bromides (PBr3, PBr5), various phosphorus iodides (PI3, P2I4), and the like; thiophosphoryl fluoride (PS F3), thiophosphoryl chloride (PSCl3), thiophosphoryl bromide (PSBr3), thiophosphoryl iodide (PSI3), thiophosphoryl fluoride dichloride (PSCl2F), thiophosphoryl fluoride dibromide (PSBr2F) and other halogenated thiophosphoryls; raw materials composed of at least two atoms selected from the above four atoms, halogen elements such as fluorine (F2), chlorine (Cl2), bromine (Br2), iodine (I2), preferably chlorine (Cl2), bromine (Br2), iodine (I2).

[0101] Substances that can be used as raw materials other than the above-mentioned ones include, for example, raw materials containing at least one atom selected from the above-mentioned four atoms and atoms other than the four atoms. More specifically, they include: lithium compounds such as lithium oxide, lithium hydroxide, and lithium carbonate; alkali metal sulfides such as sodium sulfide, potassium sulfide, rubidium sulfide, and cesium sulfide; metal sulfides such as silicon sulfide, germanium sulfide, boron sulfide, gallium sulfide, tin sulfide (SnS, SnS2), aluminum sulfide, and zinc sulfide; phosphoric acid compounds such as sodium phosphate and lithium phosphate; halides of alkali metals other than lithium such as sodium iodide, sodium fluoride, sodium chloride, and sodium bromide; metal halides such as aluminum halides, silicon halides, germanium halides, arsenic halides, selenium halides, tin halides, antimony halides, tellurium halides, and bismuth halides; halogenated phosphorus oxides such as phosphorus oxychloride (POCl3) and phosphorus oxybromide (POBr3); and the like.

[0102] Among the above, preferred are: lithium sulfide; phosphorus sulfide such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); halogen elements such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2); lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide. In addition, when oxygen atoms are introduced into the solid electrolyte, lithium oxide, lithium hydroxide, and phosphoric acid compounds such as lithium phosphate are preferred.

[0103] As the halogen atom, a chlorine atom, a bromine atom and an iodine atom are preferred, and at least one selected from these is preferred.

[0104] Therefore, as the above-mentioned lithium halide, lithium chloride, lithium bromide, and lithium iodide are preferred, and as the halogen element, chlorine (Cl2), bromine (Br2), and iodine (I2) are preferred. In addition, they can be used alone or in combination of multiple types.

[0105] As the combination of raw materials, for example, preferably there can be mentioned a combination of lithium sulfide, elemental sulfur, phosphorus pentasulfide and lithium halide, and a combination of lithium sulfide, elemental sulfur, phosphorus pentasulfide and a halogen element. As the lithium halide, preferably there is lithium chloride, lithium bromide and lithium iodide. As the halogen element, preferably there is chlorine, bromine and iodine.

[0106] In this embodiment, Li3PS4 including a PS4 structure can also be used as a part of the raw material. Specifically, Li3PS4 and the like are prepared first and used as the raw material.

[0107] The content of Li3PS4 relative to the total of the raw materials is preferably 60 to 100 mol%, more preferably 65 to 90 mol%, and further preferably 70 to 80 mol%.

[0108] In addition, when Li3PS4 and a halogen element are used, the content of the halogen element relative to Li3PS4 is preferably 1 to 50 mol%, more preferably 10 to 40 mol%, further preferably 20 to 30 mol%, and further preferably 22 to 28 mol%.

[0109] The lithium sulfide used in this embodiment is preferably in the form of particles.

[0110] The average particle size of lithium sulfide particles (D 50 ) is preferably 0.1 μm to 1000 μm, more preferably 0.5 μm to 100 μm, and even more preferably 1 μm to 20 μm. In this specification, the average particle size (D 50 ) is the particle size when the particle size distribution cumulative curve is drawn from the particle with the smallest particle size to 50% (volume basis) of the whole, and the volume distribution is, for example, the average particle size that can be measured using a laser diffraction / scattering particle size distribution measuring device. In addition, among the raw materials exemplified as the above raw materials, the solid raw material preferably has an average particle size of the same degree as the above lithium sulfide particles. That is, it is preferably within the same range as the average particle size of the above lithium sulfide particles.

[0111] (About the blending ratio of raw materials)

[0112] In the production method of the present embodiment, the amount of elemental sulfur used is not particularly limited and may be determined according to the desired sulfide solid electrolyte, the types and amounts of the raw material contents used, and the like.

[0113] For example, it can also be determined according to the type of solvent used, and can be classified according to the amount of elemental sulfur used relative to 1.0 mol of lithium sulfide. When an organic solvent such as an ether solvent or an alcohol solvent is used and the content of the organic solvent is 60% by volume or more based on the total amount of the solvent, the amount of elemental sulfur used is preferably set to more than 1.0 mol or less, and more preferably less than 1.0 mol, relative to 1.0 mol of lithium sulfide.

[0114] When the solvent is an organic solvent such as an ether solvent or an alcohol solvent, the amount of elemental sulfur used is preferably more than 1.0 mol or less than 1.0 mol relative to 1.0 mol of lithium sulfide.

[0115] On the other hand, when the amount of elemental sulfur used exceeds 1.0 mol relative to 1.0 mol of lithium sulfide, an organic solvent such as an ether solvent or an alcohol solvent may be used as the solvent and the content of the organic solvent may be 60% by volume or more based on the total amount of the solvent. The higher the content of the organic solvent such as an ether solvent or an alcohol solvent, the more preferred it is, and an ether solvent or an alcohol solvent is more preferred. The content of the organic solvent will be described in detail later.

[0116] In addition, when the amount of elemental sulfur used is 1.0 mol or less relative to 1.0 mol of lithium sulfide, an organic solvent such as an ether solvent or an alcohol solvent may be used as the solvent and the content of the organic solvent may be 60% by volume or more based on the total amount of the solvent. In addition to the ether solvent and the alcohol solvent, other solvents described below may or may not be included. The details of the content of the organic solvent will be described below.

[0117] In the case where the amount of elemental sulfur used exceeds 1.0 mole relative to 1.0 mole of lithium sulfide and is used in excess, it is preferably 1.1 moles or more, more preferably 1.3 moles or more, and further preferably 1.4 moles or more. There is no particular restriction on the upper limit, and it can be set to about 4.0 moles or less, preferably 3.0 moles or less, more preferably 2.5 moles or less, and further preferably 2.2 moles or less. In addition, in the case of wanting to obtain a sulfide solid electrolyte having a type II crystal structure in the sulfide crystal lithium superion conductor region, as an upper limit, in addition to the above upper limit, it is also preferably 1.9 moles or less, and more preferably 1.7 moles or less. In the case of excessive use of elemental sulfur, if its usage is within the above range, a sulfide solid electrolyte with improved ionic conductivity can be manufactured more efficiently.

[0118] In this case, the amount of elemental sulfur used is preferably 140% or more, more preferably 150% or more, relative to the sulfur atoms required for the composition of the sulfide solid electrolyte to be obtained by the production method of the present embodiment. The upper limit is not particularly limited, but from the viewpoint of more efficiently obtaining a sulfide solid electrolyte, it may be about 300% or less, preferably 280% or less, more preferably 250% or less, and even more preferably 200% or less.

[0119] When the amount of elemental sulfur used is 1.0 mol or less relative to 1.0 mol of lithium sulfide, the upper limit is preferably 1.0 mol or less, and the lower limit is preferably 0.2 mol or more, more preferably 0.3 mol or more, and further preferably 0.45 mol or more. When the amount of elemental sulfur used is within the above range, a sulfide solid electrolyte with improved ion conductivity can be produced more efficiently.

[0120] In this case, the amount of elemental sulfur used is preferably 105% or more, more preferably 110% or more, and even more preferably 115% or more, relative to the sulfur atoms required to form the composition of the sulfide solid electrolyte to be obtained by the production method of the present embodiment. The upper limit is not particularly limited, but may be less than 140% from the viewpoint of more efficiently obtaining a sulfide solid electrolyte.

[0121] When lithium sulfide, elemental sulfur, phosphorus pentasulfide and lithium halide are used as raw materials, from the viewpoint of obtaining higher chemical stability and higher ion conductivity, the ratio of lithium sulfide to the total of lithium sulfide and phosphorus pentasulfide is preferably 65 to 85 mol%, more preferably 70 to 82 mol%, and even more preferably 74 to 80 mol%.

[0122] When lithium sulfide, elemental sulfur, phosphorus pentasulfide, lithium halide and other raw materials used as needed are used, the content of lithium sulfide and phosphorus pentasulfide relative to the total of these raw materials is preferably 50 to 99 mol%, more preferably 55 to 90 mol%, and even more preferably 60 to 85 mol%.

[0123] When lithium bromide and lithium iodide are used in combination as the lithium halide, from the viewpoint of improving ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 80 mol%, further preferably 35 to 80 mol%, and particularly preferably 45 to 70 mol%.

[0124] In addition, when lithium bromide and lithium chloride are used in combination as lithium halide, from the viewpoint of improving ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium chloride is preferably 1 to 99 mol%, more preferably 15 to 75 mol%, further preferably 25 to 60 mol%, and particularly preferably 35 to 45 mol%.

[0125] When a halogen element is used as a raw material and lithium sulfide, elemental sulfur, and phosphorus pentasulfide are used, the ratio of the number of moles of lithium sulfide obtained by removing the same number of moles of lithium sulfide as the number of moles of the halogen element to the total number of moles of lithium sulfide and phosphorus pentasulfide obtained by removing the same number of moles of lithium sulfide as the number of moles of the halogen element is preferably in the range of 60 to 90%, more preferably in the range of 65 to 85%, further preferably in the range of 68 to 82%, further preferably in the range of 72 to 78%, and particularly preferably in the range of 73 to 77%. This is because these ratios can obtain higher ion conductivity.

[0126] Furthermore, from the same viewpoint, when lithium sulfide, elemental sulfur, phosphorus pentasulfide and a halogen element are used, the content of the halogen element relative to the total amount of lithium sulfide, phosphorus pentasulfide and the halogen element is preferably 1 to 50 mol%, more preferably 2 to 40 mol%, further preferably 3 to 25 mol%, and further preferably 3 to 15 mol%.

[0127] When lithium sulfide, elemental sulfur, phosphorus pentasulfide, a halogen element and a lithium halide are used, the content of the halogen element relative to the total amount of lithium sulfide, phosphorus pentasulfide, the halogen element and the lithium halide (α mol%) and the content of the lithium halide relative to the total amount of these (β mol%) preferably satisfy the following formula (2), more preferably satisfy the following formula (3), further preferably satisfy the following formula (4), and further preferably satisfy the following formula (5).

[0128] 2≤2α+β≤100…(2)

[0129] 4≤2α+β≤80…(3)

[0130] 6≤2α+β≤50…(4)

[0131] 6≤2α+β≤30…(5)

[0132] When two halogens are used as single substances, if the number of moles of one halogen atom in the substance is set to A1, and the number of moles of the other halogen atom in the substance is set to A2, then A1:A2 is preferably 1:99 to 99:1, more preferably 10:90 to 90:10, further preferably 20:80 to 80:20, and further preferably 30:70 to 70:30.

[0133] When two halogen elements are used and the two halogen elements are bromine and iodine, if the number of moles of bromine is set to A1 and the number of moles of iodine is set to A2, then A1:A2 is preferably 1:99 to 99:1, more preferably 20:80 to 80:20, further preferably 35:65 to 80:20, and further preferably 45:55 to 70:30.

[0134] Furthermore, when the two halogen elements are bromine and chlorine, if the number of moles of bromine is set to B1 and the number of moles of chlorine is set to B2, then B1:B2 is preferably 1:99 to 99:1, more preferably 15:85 to 75:25, further preferably 25:75 to 60:40, and further preferably 35:45 to 65:55.

[0135] (Solvent)

[0136] The solvent used when mixing the above raw materials contains an organic solvent of ether solvent and alcohol solvent in an amount of 60% by volume or more based on the total amount of the solvent.

[0137] The content of the organic solvent as an ether solvent and an alcohol solvent is preferably 70% by volume or more, more preferably 80% by volume or more, further preferably 90% by volume or more, and further preferably 95% by volume or more. In addition, it is particularly preferably 100% by volume, that is, the solvent used when mixing the above raw materials is preferably an organic solvent of an ether solvent and an alcohol solvent. If the content of the above organic solvent is within the above range, the generation of sulfur active species such as sulfur radicals suitable for the formation of an electrolyte precursor can be promoted in a well-balanced manner, and the formation of an electrolyte precursor (polysulfide) can be further promoted, and a sulfide solid electrolyte with improved ion conductivity can be manufactured more efficiently.

[0138] Above-mentioned solvent and use ether solvent and alcohol solvent, and the content of these organic solvents is calculated as more than 60 volume % based on the total amount of solvent, and can also comprise other solvents described later.In addition, as mentioned above, also preferably these organic solvents are 100 volume %, that is, the total amount of solvent is the organic solvent of ether solvent and alcohol solvent.Here, in the scheme that these organic solvents are 100 volume %, as a matter of course include the situation that solvent is ether solvent and alcohol solvent as described in text, namely only use the organic solvent of ether solvent and alcohol solvent as the scheme of solvent, also include the scheme that comprises other solvents that inevitably mix into.In this case, the content of other solvents is below 3 volume %, and then is below 2 volume %, below 1 volume %, below 0.5 volume %, below 0.1 volume %.

[0139] (Alcohol solvent)

[0140] Examples of the alcohol solvent include aliphatic alcohols, alicyclic alcohols, heterocyclic alcohols and aromatic alcohols. In view of availability and cost, aliphatic alcohols, alicyclic alcohols and aromatic alcohols are preferred, and aliphatic alcohols are more preferred.

[0141] As the aliphatic alcohol, for example, representative and preferred examples include: saturated or unsaturated monovalent aliphatic alcohols such as methanol, ethanol, various propanols, allyl alcohol, various butanols, and various butenols; saturated or unsaturated polyvalent aliphatic alcohols such as various propylene glycols, various propylene glycols, various butanediols, various butene glycols, various hexanediols, various hexene glycols, various butanetriols, erythritol, pentaerythritol, and dipentaerythritol.

[0142] In this specification, for example, in the case of various butanols, "various" means that all conceivable isomers such as 1-butanol, 2-butanol, 2-methyl-1-propanol, and 1,1-dimethylethanol are included. In addition, even if "various" is not marked, compounds described in a form without specifying the substitution position number also include all conceivable isomers.

[0143] The aliphatic hydrocarbon group in the aliphatic alcohol may be linear or branched, and may be saturated or unsaturated.

[0144] The carbon number of the aliphatic alcohol is preferably 1 or more, more preferably 2 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, and further preferably 4 or less.

[0145] The aliphatic alcohol may be a partially substituted aliphatic alcohol, and preferred examples include alkanolamines partially substituted with amino groups such as ethanolamine, propanolamine, and dimethylethanolamine; and alcohols partially substituted with halogen atoms such as fluoroalcohols.

[0146] Representative examples of the alicyclic alcohol include: monovalent or polyvalent saturated or unsaturated monocyclic alicyclic alcohols such as cyclopropanol, methylcyclopropanol, cyclopropanemethanol, cyclobutanol, cyclobutenol, cyclopentanol, cyclopentenol, cyclohexanol, methylcyclohexanol, cyclohexenol, cyclohexanediol, and cyclohexanetriol; and monovalent or polycyclic alicyclic alcohols such as cyclopentylcyclopentanol, cyclohexylcyclohexanol, cyclohexylphenylcyclohexanol, and dicyclohexanol.

[0147] The carbon number of the alicyclic alcohol is preferably 3 or more, and the upper limit is preferably 12 or less, more preferably 10 or less, and further preferably 8 or less.

[0148] The alicyclic alcohol may be partially substituted, and preferably, alicyclic alcohols partially substituted with saturated or unsaturated hydrocarbon groups (including linear and branched hydrocarbon groups) such as alkyl and alkenyl groups, for example, alicyclic alcohols partially substituted with amino groups such as aminomethylcyclopropanol, and alicyclic alcohols partially substituted with halogen atoms, etc. In addition, alicyclic alcohols substituted with substituents such as amide groups and cyano groups may be mentioned.

[0149] Representative examples of the heterocyclic alcohol include monocyclic alcohols such as oxetane alcohol, oxetane methanol, furfuryl alcohol, tetrahydrofurfuryl alcohol, tetrahydropyran methanol, morpholine alcohol, and pyridine methanol; and polycyclic condensed heterocyclic alcohols such as benzofuran methanol and dihydrobenzofuran methanol.

[0150] The number of carbon atoms in the heterocyclic alcohol is preferably 3 or more, and the upper limit is preferably 24 or less, more preferably 18 or less, and further preferably 12 or less.

[0151] The heterocyclic alcohol can be obtained by substituting a part of the alicyclic alcohol in the same manner as the above-mentioned alicyclic alcohol.

[0152] Representative and preferred examples of the aromatic alcohol include: monocyclic aromatic alcohols such as benzyl alcohol, salicyl alcohol, benzyl alcohol, methoxyphenyl alcohol, trimethoxyphenyl alcohol, and phenylethyl alcohol; polycyclic aromatic alcohols such as diphenyl alcohol and triphenyl alcohol; and condensed polycyclic aromatic alcohols such as naphthalene alcohol, anthracene alcohol, benzofuran alcohol, and dihydrobenzofuran alcohol.

[0153] The number of carbon atoms in the aromatic alcohol is preferably 7 or more, and the upper limit is preferably 24 or less, more preferably 20 or less, and further preferably 16 or less.

[0154] The aromatic alcohol can be obtained by partially substituting the alicyclic alcohol in the same manner as the above-mentioned alicyclic alcohol.

[0155] The above examples are merely representative examples of preferred alcohol solvents, and the solvents that can be used in the production method of the present embodiment are not limited to the above examples.

[0156] The alcohol solvent may be any of primary alcohol, secondary alcohol and tertiary alcohol, preferably primary alcohol. In addition, the alcohol solvent may be a monohydric alcohol having one hydroxyl group or a polyhydric alcohol having two or more hydroxyl groups, preferably a monohydric alcohol.

[0157] (Ether solvent)

[0158] Examples of the ether solvent include aliphatic ethers, alicyclic ethers, heterocyclic ethers and aromatic ethers. In view of availability and cost, aliphatic ethers, alicyclic ethers and aromatic ethers are preferred, aliphatic ethers and alicyclic ethers are more preferred, and alicyclic ethers are further preferred.

[0159] As the aliphatic ether, representative and preferred examples include: monoethers such as dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, and tert-butyl methyl ether; diethers such as dimethoxymethane, dimethoxyethane, diethoxymethane, and diethoxyethane; polyethers having three or more ether groups such as diethylene glycol dimethyl ether (diglyme) and triethylene glycol dimethyl ether (triglyme); and ethers containing hydroxyl groups such as diethylene glycol and triethylene glycol.

[0160] The carbon number of the aliphatic ether is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less.

[0161] Furthermore, the aliphatic alcohol may be linear or branched.

[0162] Representative examples of the alicyclic ethers include monocyclic alicyclic ethers such as ethylene oxide, propylene oxide, furan, tetrahydrofuran, pyran, tetrahydropyran, dimethoxytetrahydrofuran, cyclopentyl methyl ether, dioxane, dioxene, dioxin, and dioxolane; and polycyclic alicyclic ethers such as dicyclopentyl ether and dicyclohexyl ether.

[0163] Typical examples of the heterocyclic ether include monocyclic heterocyclic ethers such as morpholine and hydroxymethyldimethoxypyridine; and polycyclic condensed heterocyclic ethers such as benzofuran, benzopyran, dibenzofuran and methoxyindole.

[0164] The carbon number of the alicyclic ether or heterocyclic ether is preferably 3 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 10 or less.

[0165] In addition, typical and preferred examples of the aromatic ether include: monocyclic aromatic ethers such as methyl phenyl ether (anisole) and ethyl phenyl ether; polycyclic aromatic ethers such as dibenzyl ether, diphenyl ether and benzyl phenyl ether; and condensed polycyclic aromatic ethers such as benzylnaphthyl ether and bisnaphthyl ether.

[0166] The number of carbon atoms in the aromatic ether is preferably 7 or more, more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 12 or less.

[0167] The ether compound used in this embodiment may be an ether compound substituted with a linear or branched hydrocarbon group such as an alkyl group or an alkenyl group, an alkoxy group (the alkyl group may be either linear or branched), a hydroxyl group, an amino group, an amide group, a cyano group or a halogen atom.

[0168] Among the above ether compounds, from the viewpoint of obtaining higher ion conductivity, alicyclic ethers are preferred, monocyclic alicyclic ethers are more preferred, and tetrahydrofuran is particularly preferred.

[0169] (Other solvents with heteroatoms)

[0170] In the manufacturing method of the present embodiment, as a solvent other than the organic solvent such as the ether solvent and alcohol solvent containing oxygen atoms, a solvent containing heteroatoms can also be used. As heteroatoms contained in the solvent, oxygen atoms, nitrogen atoms, sulfur atoms, chlorine atoms, phosphorus atoms, etc. can be preferably exemplified, among which oxygen atoms and nitrogen atoms are preferred. As solvents containing heteroatoms, they can contain one of these heteroatoms or multiple kinds.

[0171] Examples of such heteroatom-containing solvents include solvents containing oxygen atoms such as ester solvents, aldehyde solvents, and ketone solvents; solvents containing nitrogen atoms such as amine solvents and nitrile solvents; and solvents containing oxygen atoms and nitrogen atoms such as amide solvents. Among the above, nitrile solvents are preferred.

[0172] (Nitrile solvent)

[0173] Examples of the nitrile solvent include aliphatic nitrile, alicyclic nitrile, heterocyclic nitrile and aromatic nitrile. In view of availability and cost, aliphatic nitrile is preferred.

[0174] As the aliphatic nitriles, representative and preferred examples include: saturated or unsaturated aliphatic nitriles having one nitrile group, such as acetonitrile, acrylonitrile, methoxyacetonitrile, propionitrile, methoxypropionitrile, butyronitrile, etc.; saturated or unsaturated aliphatic nitriles having two or more nitrile groups, such as propane dinitrile, propane trinitrile, butane dinitrile, butene dinitrile, butane trinitrile, pentane dinitrile, pentane trinitrile, hexane dinitrile, hexene dinitrile, hexane trinitrile, methylene pentane dinitrile, etc.

[0175] The carbon number of the aliphatic nitrile is preferably 2 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and further preferably 4 or less. In addition, the carbon number of the aliphatic hydrocarbon group in the aliphatic nitrile is preferably 1 or more, and the upper limit is preferably 8 or less, more preferably 6 or less, and further preferably 2 or less.

[0176] Furthermore, the aliphatic hydrocarbon group in the aliphatic nitrile may be linear or branched.

[0177] The nitrile solvent may be substituted with a linear or branched hydrocarbon group such as an alkyl group or an alkenyl group, an alkoxy group (the alkyl group may be linear or branched), a hydroxyl group, an amino group, an amide group, a cyano group or a halogen atom.

[0178] In addition, as for the amine solvents and amide solvents exemplified, for example, heterocyclic aromatic amine solvents such as pyridine; and amide solvents such as dimethylformamide, dimethylacetamide, hexamethylphosphoramide, and N-methylpyrrolidone may be preferably mentioned.

[0179] (Other solvents)

[0180] In the manufacturing method of this embodiment, as a solvent and as other solvents other than the organic solvents of the above-mentioned ether solvents and alcohol solvents, in addition to the above-mentioned other solvents containing heteroatoms, hydrocarbon solvents can also be used. As hydrocarbon solvents, for example, aliphatic hydrocarbon solvents such as hexane, pentane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane, and tridecane; alicyclic hydrocarbon solvents such as cyclohexane and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, mesitylene, ethylbenzene, and tert-butylbenzene can be used.

[0181] In this case, the usage amount of other solvents is less and more preferred, for example, relative to the usage amount of 100.0 parts by volume of the above-mentioned organic solvents (i.e. the organic solvents of ether solvents and alcohol solvents), it is preferably below 50.0 parts by volume, more preferably below 30.0 parts by volume, and further preferably below 15.0 parts by volume. In addition, it is certainly preferred not to use other solvents and only use the above-mentioned organic solvent, but as mentioned above, in this case, it is also possible to inevitably include the solvent beyond the above-mentioned organic solvent.

[0182] (Amount of solvent used)

[0183] In the case of using an alcohol solvent, the amount of the alcohol solvent used is preferably 0.030 mol or more, more preferably 0.035 mol or more, further preferably 0.040 mol or more, and further preferably 0.045 mol or more relative to 1.0 mol of lithium sulfide used as a raw material. There is no particular upper limit, but considering efficiency, it can be set to 5.0 mol or less, preferably 3.5 mol or less. In addition, in the case of obtaining a sulfide solid electrolyte having a sulfide crystal lithium superion conductor region type II crystal structure, as an upper limit, in addition to the above upper limit, it is also preferably 3.0 mol or less, more preferably 2.5 mol or less, further preferably 1.0 mol or less, further preferably 0.7 mol or less, and particularly preferably 0.5 mol or less. If the amount of the alcohol solvent used is within the above range, the generation of sulfur active species such as sulfur radicals suitable for the formation of the electrolyte precursor can be promoted in a well-balanced manner, and the formation of the electrolyte precursor (polysulfide) can be further promoted, and the sulfide solid electrolyte with improved ion conductivity can be more efficiently manufactured.

[0184] When an ether solvent is used, the content of the ether solvent based on the total amount of the solvent is preferably 50.0 volume % or more, more preferably 75.0 volume % or more, further preferably 90.0 volume % or more, further preferably 95.0 volume % or more, and particularly preferably 98.0 volume % or more. In addition, in the case of obtaining a sulfide solid electrolyte having a sulfide crystal lithium superion conductor region type II crystal structure, as a lower limit, in addition to the above lower limit, it is also preferably 99.0 volume % or more, 99.5 volume % or more. In addition, if the amount of the ether solvent used is within the above range, the generation of sulfur active species such as sulfur radicals suitable for the formation of the electrolyte precursor can be promoted in a well-balanced manner, and the formation of the electrolyte precursor (polysulfide) can be further promoted, and a sulfide solid electrolyte with improved ion conductivity can be manufactured more efficiently.

[0185] The ratio of the amount of the ether solvent used to the amount of the alcohol solvent used (ether solvent / alcohol solvent (volume ratio)) is usually 30 or more, preferably 50 or more. In addition, in the case of obtaining a sulfide solid electrolyte having a sulfide crystalline lithium superion conductor region type II crystal structure, as a lower limit, in addition to the above lower limit, it is preferably 150 or more, more preferably 200 or more, and further preferably 250 or more. In addition, as an upper limit, it is preferably 2500 or less, more preferably 2300 or less, and further preferably 1100 or less. If the ratio is within the above range, the generation of sulfur active species such as sulfur radicals suitable for the formation of the electrolyte precursor can be promoted in a well-balanced manner, the formation of the electrolyte precursor (polysulfide) can be further promoted, and a sulfide solid electrolyte with improved ion conductivity can be produced more efficiently.

[0186] In addition, as the amount of solvent used, it is preferably 500mL or more, more preferably 1000mL or more, and further preferably 1500mL or more relative to 100g of raw material content, and the upper limit is usually set to 5000mL or less. In addition, in the case of wanting to obtain a sulfide solid electrolyte having a sulfide crystallized lithium superion conductor region type II crystal structure, as an upper limit, in addition to the above upper limit, it is also preferably 4500mL or less, and further preferably 4000mL or less. If the amount of solvent used is within the above range, it is possible to promote the generation of active species of sulfur such as sulfur radicals suitable for the formation of electrolyte precursors in a well-balanced manner, further promote the formation of electrolyte precursors (polysulfides), and more efficiently manufacture sulfide solid electrolytes with improved ionic conductivity.

[0187] (mix)

[0188] The manufacturing method of this embodiment mixes the raw material content containing the raw material in the above-mentioned solvent. By mixing the raw material content in the solvent, the generation of sulfur active species such as sulfur radicals is promoted in a well-balanced manner, and the formation of the electrolyte precursor is promoted, so that a sulfide solid electrolyte with less impurities and high ion conductivity can be efficiently obtained.

[0189] There is no particular limitation on the method of mixing the raw material contents in the solvent, as long as the solvent and the raw material contents are put into a device capable of mixing the raw material contents in the solvent for mixing. For example, it is preferred to supply the solvent to the tank, and after the stirring blade is operated, the raw material contents are gradually added. In addition, it is also preferred to supply the raw material contents to the tank, and after the stirring blade is operated, the solvent is gradually added. Since a good mixing state of the raw material contents can be obtained, the dispersibility of the raw material is improved, the generation of sulfur active species such as sulfur radicals suitable for the formation of the electrolyte precursor is promoted in a well-balanced manner, and the formation of the electrolyte precursor (polysulfide) is promoted.

[0190] However, when a halogen element is used as a raw material, the raw material is sometimes not solid. Specifically, at normal temperature and pressure, fluorine and chlorine become gases, and bromine becomes liquid. In such a case, for example, when the raw material is liquid, it can be supplied to the tank together with the solvent separately from other solid raw materials. In addition, when the raw material is gas, it can be supplied in a manner of blowing into a substance obtained by adding a solid raw material to a solvent.

[0191] The order in which the raw materials containing the raw materials are added and mixed is not particularly limited, but in consideration of work efficiency, all the raw materials are preferably added at the same time and mixed at once.

[0192] In addition, if considering improving the solubility of the raw materials, further suppressing the generation of impurities, and more efficiently obtaining a sulfide solid electrolyte with high ion conductivity, it is preferred to divide the raw materials into two raw material groups, raw material group 1 and raw material group 2, and mix them in batches by mixing raw material group 1 and then raw material group 2.

[0193] When batch mixing is performed, the raw material group 1 preferably contains elemental sulfur. The generation of active sulfur species such as sulfur radicals suitable for forming an electrolyte precursor is promoted in a well-balanced manner, and a sulfide solid electrolyte having high ion conductivity can be obtained more efficiently.

[0194] From the same viewpoint, the combination of raw material group 1 and raw material group 2 is preferred, wherein raw material group 1 includes a raw material including at least one atom selected from lithium atoms, phosphorus atoms and sulfur atoms, and elemental sulfur and lithium sulfide, and raw material group 2 includes a raw material including a halogen atom. This is because raw material group 1 includes elemental sulfur and lithium sulfide, and thus, through the reaction of these, the formation of sulfur active species such as sulfur radicals suitable for forming an electrolyte precursor with other raw materials is promoted in a well-balanced manner through lithium polysulfide. In addition, from the same viewpoint, the combination of raw material group 1 and raw material group 2 is also preferred, wherein raw material group 1 includes a raw material including a halogen atom, elemental sulfur and lithium sulfide, and raw material group 2 includes a raw material including a phosphorus atom and a sulfur atom.

[0195] In the production method of the present embodiment, the order of charging and mixing the raw materials may be selected according to whether priority is given to work efficiency or to the ion conductivity of the sulfide solid electrolyte.

[0196] In addition, as described above, in the manufacturing method of the present embodiment, as a raw material included in the raw material content, Li3PS4 or the like containing a PS4 structure can be prepared and used. Li3PS4 can be manufactured by, for example, mixing lithium sulfide and phosphorus pentasulfide at a molar ratio of 75:25, respectively. In the manufacturing method of the present embodiment, when phosphorus pentasulfide is used as a raw material in addition to lithium sulfide, a raw material group containing lithium sulfide and phosphorus pentasulfide and elemental sulfur at a specified molar ratio of 75:25 or the like can be mixed in a solvent as raw material group 1, and then a raw material containing halogen atoms such as lithium halide, other remaining raw materials required for manufacturing the desired sulfide solid electrolyte, such as a raw material group containing the insufficient part of lithium sulfide, is added as raw material group 2 and mixed. By pre-forming an electrolyte precursor (polysulfide) containing the basic structure of Li3PS4, a sulfide solid electrolyte can be obtained more efficiently.

[0197] Here, the predetermined molar ratio of the lithium sulfide to the phosphorus pentasulfide is preferably 55 to 85:15 to 45, more preferably 60 to 80:20 to 40, and even more preferably 65 to 75:25 to 35.

[0198] The manufacturing method of the present embodiment is characterized in that it includes: mixing the raw material content in the solvent. That is, the raw material content only needs to be mixed without crushing, so it is possible to manufacture by a method that does not use a device generally referred to as a crusher, such as a media crusher such as a ball mill or a bead mill, which is used for the purpose of crushing the solid electrolyte raw material. In the manufacturing method of the present embodiment, the solvent and the raw material can be mixed only by simply mixing the raw material content in the solvent to generate a polysulfide as an electrolyte precursor, and by decomposing it by heating or the like, an amorphous sulfide solid electrolyte can be formed, and then a crystalline sulfide solid electrolyte can be formed.

[0199] In order to shorten the mixing time for obtaining the electrolyte precursor or to pulverize the mixture of the raw materials in the solvent, a pulverizer may be used. However, as described above, it is preferred not to use a pulverizer.

[0200] As a device for mixing the raw material content in the solvent, for example, a mechanical stirring mixer with stirring blades in a tank can be cited. The mechanical stirring mixer can be exemplified by a high-speed stirring mixer, a double-arm mixer, etc., and from the viewpoint of improving the uniformity of the raw materials in the mixture of the raw material content and obtaining higher ion conductivity, a high-speed stirring mixer is preferably used. In addition, as a high-speed stirring mixer, a vertical axis rotating mixer, a horizontal axis rotating mixer, etc. can be cited, and any type of mixer can also be used.

[0201] As the shape of the stirring blade used in the mechanical stirring mixer, anchor type, blade type, arm type, belt type, multi-stage blade type, two-arm type, bucket type, biaxial blade type, flat blade type, C-type blade type etc. can be exemplified, from the viewpoint of improving the uniformity of solid electrolyte raw materials, obtaining higher ionic conductivity, preferably use bucket type, flat blade type, C-type blade type. In addition, in the mechanical stirring mixer, preferably set the circulation line that returns to the inside of the mixer again after the stirring object is discharged to the outside of the mixer. Thus, the raw materials with heavier specific gravity such as lithium halides will not precipitate and will not be stirred by retention, and more uniform mixing can be carried out.

[0202] Although the location of the circulation line is not particularly limited, it is preferably located at a location where the liquid is discharged from the bottom of the mixer and returned to the upper part of the mixer. Thus, the solid electrolyte raw material that is easy to precipitate is easily stirred evenly with the convection of the circulation. Furthermore, the return port is preferably located below the liquid surface of the stirring object. Thus, it is possible to suppress liquid splashing and cause the stirring object to adhere to the wall surface inside the mixer.

[0203] There is no particular upper limit to the mixing time when mixing the raw material content in the solvent. Taking efficiency into consideration, it is preferably 240 minutes or less, more preferably 60 minutes or less, further preferably 30 minutes or less, and further preferably 15 minutes or less. The lower limit is usually 0.1 minutes or more, preferably 1 minute or more, and further preferably 3 minutes or more.

[0204] The temperature conditions for mixing the raw material content in the solvent are not particularly limited, but are, for example, -30 to 100°C, preferably -10 to 50°C, and more preferably about room temperature (23°C) (eg, about room temperature ±5°C).

[0205] 〔heating〕

[0206] The production method of this embodiment includes: heating after mixing the raw material content. By heating, the generated polysulfide can be decomposed, the solvent can be removed, and the elemental sulfur generated by the decomposition of the polysulfide can be removed and crystallized. In addition, although the elemental sulfur can be removed by heating, a different method such as solvent washing and hydrodesulfurization can be used for the removal of the elemental sulfur.

[0207] The heating temperature is not particularly limited as long as it is room temperature or higher. The room temperature may vary and therefore cannot be generally defined, but it is usually preferably 20° C. or higher.

[0208] In addition, the upper and lower limits of the heating temperature can be changed according to the type of sulfide solid electrolyte to be obtained, the type and amount of solvent used in mixing, etc., so it cannot be generalized. It is preferably above room temperature (20°C), and the upper limit is preferably below 500°C. If the heating temperature is within the above range, the decomposition of polysulfides, the removal of solvents and the removal of elemental sulfur can be more efficiently performed and crystallization can be performed. In addition, in the case of obtaining a sulfide solid electrolyte having an argyrodite-type crystal structure, as an upper limit, it is preferably set to the temperature of the above upper limit. In the case of obtaining a sulfide solid electrolyte having a sulfide crystal lithium superion conductor region type II crystal structure, as an upper limit, in addition to the above upper limit, it is also preferably set to 300°C or less.

[0209] Furthermore, when heating, it is preferable to perform heating in multiple stages. For example, it is preferable to perform heating (first heating) mainly for decomposing the generated polysulfide, removing the solvent and removing the elemental sulfur, and then perform heating (second heating) for crystallization. More specifically, it is preferable to perform first heating at a heating temperature of 20°C or higher and lower than 150°C and second heating at a heating temperature of 150°C or higher and 500°C or lower.

[0210] The heating temperature in the first heating may be 20° C. or higher and lower than 150° C. For example, the first heating may be performed by heating at a lower temperature and then heating at a higher temperature, that is, by heating in multiple stages.

[0211] Generally, the removal of the solvent starts at 20°C or higher, the decomposition of the polysulfide starts at 60°C or higher, and the removal of sulfur starts at 100°C or higher. By performing multi-stage heating at heating temperatures corresponding to these purposes, each purpose can be more efficiently achieved, so it is easy to obtain a sulfide solid electrolyte with improved ion conductivity. In particular, with respect to the removal of elemental sulfur, by reliably performing this removal, the generation of impurities caused by the residual elemental sulfur can be further suppressed, so it is easy to obtain a sulfide solid electrolyte with improved ion conductivity.

[0212] For example, the heating temperature when heating at a lower temperature (first heating-1) is preferably 20° C. or higher, and the upper limit is preferably lower than 60° C., more preferably 50° C. or lower. By setting the temperature in such a range, the solvent can be removed.

[0213] Next, the heating temperature when heating at a higher temperature (first heating-2) is preferably 60° C. or higher, more preferably 65° C. or higher, further preferably 75° C. or higher, further preferably 95° C. or higher, and particularly preferably 110° C. or higher, and the upper limit is lower than 150° C., more preferably 145° C. or lower, further preferably 135° C. or lower, and further preferably 130° C. or lower. By setting the temperature in such a range, decomposition of polysulfides and removal of sulfur can be mainly performed.

[0214] As described above, the first heating can remove the solvent, decompose the polysulfide, and remove the sulfur depending on the heating temperature, so various methods can be adopted by adjusting the heating temperature. For example, if the heating temperature of the first heating is set to 60°C or more (lower than 100°C), the solvent can be removed and the polysulfide can be decomposed, so it is set as the first heating-1, and the sulfur can be removed by heating at 100°C or more (lower than 150°C) as the first heating-2. In this case, the first heating-2 can be omitted, and the sulfur can be removed by a method other than heating, that is, solvent washing, hydrodesulfurization, etc., as described above, and then the second heating can be performed. In addition, the method of solvent washing, hydrodesulfurization, etc. for removing sulfur will be described later.

[0215] In addition, for example, the following three-stage heating can be performed: if the heating temperature of the first heating is set to 20°C or higher (lower than 60°C), the solvent can be removed, so it is set as the first heating-1, if it is heated at 60°C or higher (lower than 100°C) as the first heating-2, polysulfide can be decomposed, and further, it is heated at 100°C or higher (lower than 150°C) as the first heating-3 to remove sulfur. In this case, it is also possible to remove sulfur by a method other than heating as described above instead of the first heating-3, and by setting the heating temperature of the first heating-2 to 100°C or higher (lower than 150°C), it is also possible to decompose polysulfide and remove sulfur at the same time.

[0216] In the above, the case where the first heating is performed by multi-stage heating is described. However, if the heating temperature of the first heating is set to 100° C. or higher, for example, the solvent can be removed, polysulfide can be decomposed, and sulfur can be removed. Therefore, multi-stage heating may not be performed.

[0217] The heating time of the first heating is not particularly limited as long as it is the time of the degree that can remove the solvent at least, for example, is preferably more than 10 minutes, more preferably more than 30 minutes, more preferably more than 45 minutes, and more preferably more than 1 hour. In addition, the upper limit of the heating time is not particularly limited, and is preferably less than 24 hours, more preferably less than 10 hours, more preferably less than 5 hours, and more preferably less than 3 hours.

[0218] As the pressure condition during the first heating, it is preferably set to normal pressure or reduced pressure. When set to reduced pressure, specifically, it is preferably 85 kPa or less, more preferably 30 kPa or less, and further preferably 10 kPa or less. As the lower limit, vacuum (0 kPa) is preferred, and if the ease of pressure adjustment is considered, it is 5 kPa or more.

[0219] In addition, the heating is preferably performed in an inert gas atmosphere (e.g., a nitrogen atmosphere, an argon atmosphere) or in a reduced pressure atmosphere (particularly in a vacuum). For example, an inert gas atmosphere containing a certain concentration of hydrogen may also be used. This is because the degradation (e.g., oxidation) of the sulfide solid electrolyte can be prevented.

[0220] The heating temperature in the second heating can be changed according to the sulfide solid electrolyte to be produced, so it cannot be generalized, but if the relationship with the first heating is taken into consideration, it can be 150°C or more and 500°C or less, and preferably 160°C or more. In addition, when it is desired to obtain a sulfide solid electrolyte having an argyrodite-type crystal structure, as a lower limit, in addition to the above lower limit, it is preferably 200°C or more, and more preferably 240°C or more. In addition, as an upper limit, it is preferably 480°C or less, more preferably 460°C or less, and further preferably 440°C or less. In addition, when it is desired to obtain a sulfide solid electrolyte having a sulfide crystal lithium superion conductor region II-type crystal structure, as an upper limit, in addition to the above upper limit, it is preferably 300°C or less, more preferably 275°C or less, and further preferably 230°C or less.

[0221] The second heating may be performed in multiple stages as in the first heating. By performing multiple stages of heating as the second heating, more reliable crystallization can be achieved.

[0222] In the case of multi-stage heating, for example, the heating temperature when heating at a lower temperature (second heating-1) is set to 150°C or more and less than 350°C, and the heating temperature when heating at a higher temperature (second heating-2) is set to 350°C or more and 500°C or less. As the lower limit of the second heating-1, it is preferably set to the temperature of the lower limit of the second heating, more preferably 200°C or more, and as the upper limit, it is preferably 300°C or less, more preferably 275°C or less. In addition, as the upper limit of the second heating-2, it is preferably set to the temperature of the upper limit of the second heating, and as the lower limit, it is preferably 370°C or more, more preferably 390°C or more, and further preferably 400°C or more.

[0223] The heating time and pressure conditions in the second heating are the same as those in the first heating, and the heating time and pressure conditions are also the same in that the second heating is preferably performed in an inert gas atmosphere.

[0224] The heating method is not particularly limited, and examples thereof include methods using various heating devices such as a hot plate, a vacuum heating device, an argon atmosphere furnace, a firing furnace, and a vacuum firing furnace. In addition, in industry, a horizontal dryer or a horizontal vibrating fluidized dryer having a heating unit and a feeding mechanism can also be used, and the method can be selected according to the amount of heating treatment.

[0225] (Sulfur Removal)

[0226] In the production method of this embodiment, sulfur removal may be performed by a method other than heating as described above. For example, when the first heating temperature is set to be lower than 100° C., sulfur removal is preferably performed by a method other than heating. Examples of the method for removing sulfur include solvent washing and hydrodesulfurization.

[0227] The method of washing with a solvent includes, for example, washing the first heated powder with a solvent that dissolves sulfur, such as an aromatic hydrocarbon solvent such as benzene, toluene, or xylene; or a sulfur-containing organic solvent such as carbon disulfide, to remove sulfur.

[0228] As a method utilizing hydrodesulfurization, the powder subjected to the first heating is mixed with a hydrodesulfurization catalyst, and hydrogen is passed through the mixture while heating at 300 to 450° C., thereby removing sulfur by a hydrodesulfurization reaction. Here, as the hydrodesulfurization catalyst, preferably, a porous catalyst containing nickel, molybdenum, cobalt, tungsten, or the like as an active metal element, such as a NiMo catalyst, a CoMo catalyst, or a NiW catalyst, can be cited.

[0229] (Amorphous sulfide solid electrolyte)

[0230] In the production method of the present embodiment, an amorphous sulfide solid electrolyte is produced by mixing the raw material contents or performing the first heating mainly for removing the solvent.

[0231] The amorphous sulfide solid electrolyte generated in the manufacturing method of this embodiment contains lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms. As representative amorphous sulfide solid electrolytes, for example, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc., can be preferably cited; solid electrolytes containing other atoms such as oxygen atoms and silicon atoms, such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI, etc. From the viewpoint of obtaining higher ionic conductivity, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc. are preferred.

[0232] The types of atoms constituting the amorphous sulfide solid electrolyte can be confirmed by, for example, an ICP emission spectrometer.

[0233] In the case where the amorphous sulfide solid electrolyte generated in the manufacturing method of this embodiment has at least Li2S-P2S5, from the viewpoint of obtaining higher ion conductivity, the molar ratio of Li2S to P2S5 is preferably 65 to 85:15 to 35, more preferably 70 to 82:18 to 30, and further preferably 74 to 80:20 to 26.

[0234] For example, when the amorphous sulfide solid electrolyte generated in the manufacturing method of the present embodiment is Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and phosphorus pentasulfide is preferably 60 to 95 mol%, more preferably 65 to 90 mol%, and further preferably 70 to 85 mol%. In addition, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, further preferably 40 to 75 mol%, and particularly preferably 45 to 60 mol%.

[0235] In addition, for example, when the amorphous sulfide solid electrolyte generated in the manufacturing method of the present embodiment is Li2S-P2S5-LiCl-LiBr, the total content of lithium sulfide and phosphorus pentasulfide is preferably 45 to 80 mol%, more preferably 50 to 75 mol%, and further preferably 55 to 70 mol%. In addition, the ratio of lithium bromide to the total of lithium bromide and lithium chloride is preferably 1 to 99 mol%, more preferably 15 to 75 mol%, further preferably 25 to 60 mol%, and particularly preferably 35 to 45 mol%.

[0236] The shape of the amorphous sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape.

[0237] The average particle size (D 50 ), for example, 0.01 μm or more, further 0.03 μm or more, 0.05 μm or more, 0.1 μm or more, and the upper limit is 200.0 μm or less, further 100.0 μm or less, 10.0 μm or less, 1.0 μm or less, 0.5 μm or less.

[0238] (Crystalline sulfide solid electrolyte)

[0239] The crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment can be a so-called glass ceramic obtained by heating an amorphous sulfide solid electrolyte to a temperature higher than the crystallization temperature, and its crystal structure can be exemplified by Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11A crystal structure, a crystal structure having peaks near 2θ=20.2° and 23.6° (for example, Japanese Patent Application Laid-Open No. 2013-16423), and the like.

[0240] Another example is Li 4-x Ge 1-x P x The S4 type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148 (7) A742-746 (2001)), and Li 4-x Ge 1-x P x S4 type thio-LISICON Region II type crystal structure (see Solid State Ionics, 177 (2006), 2721-2725). From the perspective of obtaining higher ionic conductivity, the crystal structure of the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment is preferably a thio-LISICON Region II type crystal structure among the above. Here, "thio-LISICON Region II type crystal structure" means Li 4-x Ge 1-x P x S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure, and Li 4-x Ge 1-x P x Any crystal structure similar to the S4 type thio-LISICON Region II type.

[0241] The crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment may be a crystalline sulfide solid electrolyte containing the above-mentioned sulfide crystallized lithium superion conductor region type II crystal structure, or may be a crystalline sulfide solid electrolyte containing the sulfide crystallized lithium superion conductor region type II crystal structure as a main crystal. From the viewpoint of obtaining higher ionic conductivity, it is preferred that the sulfide crystallized lithium superion conductor region type II crystal structure be contained as a main crystal. In this specification, "containing as a main crystal" means that the proportion of the target crystal structure in the crystal structure is 80% or more, preferably 90% or more, and more preferably 95% or more. In addition, from the viewpoint of obtaining higher ionic conductivity, the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment preferably does not contain crystalline Li3PS4 (β-Li3PS4).

[0242] In the X-ray diffraction measurement using CuKα rays, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ=17.5°, 18.3°, 26.1°, 27.3°, and 30.0°; the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ=16.9°, 27.1°, and 32.5°; the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ=15.3°, 25.2°, 29.6°, and 31.0°; and the diffraction peaks of the Li7P3S 11 The diffraction peaks of the crystal structure appear near 2θ=17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°, for example. 4-x Ge 1-x P x The diffraction peaks of the S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure appear near 2θ=20.1°, 23.9°, and 29.5°, which are similar to Li 4-x Ge 1-x P x The diffraction peaks of the S4 type thio-LISICON Region II-type crystal structure appear near 2θ=20.2° and 23.6°, for example. These peak positions may fluctuate within a range of ±0.5°.

[0243] A crystalline sulfide solid electrolyte having the following crystal structure can also be preferably exemplified: an argyrodite-type crystal structure having the structural skeleton of the above-mentioned Li7PS6 and in which a part of P is substituted with Si.

[0244] As the composition formula of the argyrodite type crystal structure, for example, the composition formula Li 7-x P 1-y Si y S6 and Li 7+x P 1- y Si y The crystal structure represented by S6 (x is -0.6 to 0.6, y is 0.1 to 0.6). The argyrodite-type crystal structure represented by the composition formula is cubic or orthorhombic, preferably cubic, and has peaks mainly appearing at 2θ=15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0° and 52.0° in X-ray diffraction measurement using CuKα rays.

[0245] As the composition formula of the argyrodite type crystal structure, the composition formula Li 7-x-2y PS6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5). The thiogermanate crystal structure represented by this composition formula is preferably cubic. In X-ray diffraction measurement using CuKα rays, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0246] In addition, as a composition formula of the thiogermanate crystal structure, the composition formula Li 7-x PS 6-x Ha x (where Ha is Cl or Br, and x is preferably 0.2 - 1.8) can also be cited. The thiogermanate crystal structure represented by this composition formula is preferably cubic. In X-ray diffraction measurement using CuKα rays, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0247] In addition, these peak positions can fluctuate within a range of ±0.5°.

[0248] There is no particular limitation on the shape of the crystalline sulfide solid electrolyte. For example, particulate form can be cited.

[0249] As the average particle diameter (D 50 ) of the particulate crystalline sulfide solid electrolyte, for example, it is 0.01 μm or more, further 0.03 μm or more, 0.05 μm or more, 0.1 μm or more. As the upper limit, it is 200.0 μm or less, further 100.0 μm or less, 10.0 μm or less, 1.0 μm or less, 0.5 μm or less.

[0250] (Use)

[0251] The sulfide solid electrolyte obtained by the manufacturing method of this embodiment has high ionic conductivity and excellent battery performance, and thus is suitable for use in batteries.

[0252] The sulfide solid electrolyte obtained by the manufacturing method of this embodiment can be used in the positive electrode layer, can also be used in the negative electrode layer, and can also be used in the electrolyte layer. In addition, each layer can be manufactured by a known method.

[0253] In addition, it is preferred that the above battery uses a current collector in addition to the positive electrode layer, electrolyte layer, and negative electrode layer. A known current collector can be used as the current collector. For example, a layer obtained by coating a substance reactive with the above solid electrolyte with Au or the like, such as Au, Pt, Al, Ti, or Cu, can be used.

[0254] Example

[0255] Next, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples at all.

[0256] (Measurement of powder XRD diffraction)

[0257] Powder X-ray diffraction (XRD) measurements were performed as follows.

[0258] The powder of the sulfide solid electrolyte obtained in the examples and comparative examples was filled into a groove with a diameter of 20 mm and a depth of 0.2 mm and flattened with glass to prepare a sample. The sample was sealed with a kapton film for XRD and measured under the following conditions in a manner that it was not in contact with air.

[0259] Measuring device: D2 PHASER, manufactured by Bruker Corporation

[0260] Tube voltage: 30kV

[0261] Tube current: 10mA

[0262] X-ray wavelength: Cu-Kα ray

[0263] Optical system: Concentration method

[0264] Slit configuration: Sola slit 4°, divergence slit 1mm, Kβ filter (Ni plate)

[0265] Detector: Semiconductor detector

[0266] Measuring range: 2θ = 10-60 degrees

[0267] Step width, scanning speed: 0.05deg, 0.05deg / second

[0268] (Measurement of ionic conductivity)

[0269] In this example, the measurement of ion conductivity was performed as follows.

[0270] The crystalline solid electrolyte obtained in the examples and comparative examples was formed into a 10 mm diameter (cross-sectional area S: 0.785 cm 2), round particles with a height (L) of 0.1 to 0.3 cm are used to make a sample. The top and bottom of the sample are taken as electrode terminals, and the AC impedance method is used for measurement at 25°C (frequency range: 5 MHz to 0.5 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency side area, the real part Z'(Ω) at the point where -Z"(Ω) is the smallest is taken as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(S / cm) is calculated according to the following formula.

[0271] R=ρ(L / S)

[0272] σ=1 / ρ

[0273] (Example 1)

[0274] In a glove box under a nitrogen atmosphere, 0.3178 g of lithium sulfide, 0.5125 g of phosphorus pentasulfide, 0.0707 g of lithium bromide, 0.1089 g of lithium iodide and 0.2218 g of elemental sulfur were mixed using a mortar and introduced into a 100-ml reaction tank together with a stirrer. Under a nitrogen atmosphere, 40.04 mL of a mixed solvent containing 0.020 mL of ethanol (EtOH) and 40.02 mL of tetrahydrofuran (THF) (ethanol:tetrahydrofuran=1.0:2001.0 (volume ratio), the total content of ethanol and tetrahydrofuran in all solvents is 100 volume %) was added, and the mixture was stirred and mixed using a magnetic stirrer for 10 minutes.

[0275] Then, using a vacuum pump and an oil bath, heating was performed under reduced pressure at room temperature (20°C) for 1 hour (first heating-1), and heating was performed under reduced pressure at 130°C for 1 hour (first heating-2). Furthermore, the powder obtained by the first heating was heated under reduced pressure at 200°C for 2 hours (second heating) to obtain a powder.

[0276] The powder obtained by heating at 130°C in the first heating and 200°C in the second heating was subjected to powder XRD diffraction measurement. The X-ray diffraction spectra of the powder obtained by heating at 130°C and 200°C are shown in FIG. Figure 1 .

[0277] Furthermore, the ion conductivity of the powder obtained by heating at 200° C. in Example 1 was measured and found to be 1.5 mS / cm.

[0278] (Examples 2 to 9)

[0279] Powders of Examples 2 to 9 were obtained in the same manner as in Example 1 except that the amounts of elemental sulfur and the solvent used were set to the conditions shown in Table 1.

[0280] The powders obtained in Examples 2 to 9 were subjected to powder XRD diffraction measurement. The X-ray diffraction spectra of the powders obtained by heating at 130° C. in Examples 2 to 7 are shown in FIG. Figure 2 The X-ray diffraction spectra of the powders obtained by heating at 200° C. in Examples 2 to 7 are shown in Figure 3 In addition, the X-ray diffraction spectra of the powders obtained by heating at 130° C. in Examples 8 and 9 are shown in Figure 6 The X-ray diffraction spectra of the powders obtained by heating at 200° C. in Examples 8 and 9 are shown in Figure 7 .

[0281] The ion conductivity of the powders obtained by heating at 200° C. in Examples 2 to 9 was measured. The results are shown in Table 1.

[0282] (Example 10)

[0283] In the glove box under argon atmosphere, use mortar that 0.2546g lithium sulfide, 0.3241g phosphorus pentasulfide and 0.3554g elemental sulfur are mixed, are imported into 100 milliliters of reaction tanks (reaction tank 1) together with stirrer.Similarly, use mortar that 0.1236g lithium chloride, 0.1520g lithium bromide are mixed, are imported into 100 milliliters of reaction tanks (reaction tank 2) different from above-mentioned together with stirrer.Under nitrogen atmosphere, in reaction tank 1, add the mixed solvent (being 59.0 volumetric parts of tetrahydrofuran (THF) with respect to 1.0 volumetric parts of ethanol (EtOH)) of 60mL ethanol (EtOH) and tetrahydrofuran (THF), stir and mix in 10 minutes with magnetic stirring apparatus.Then, in reaction tank 2, add the solution of reaction tank 1, further stir and mix in 10 minutes with magnetic stirring apparatus.

[0284] Then, using a vacuum pump and an oil bath, heating was performed at room temperature (20°C) under reduced pressure for 1 hour (first heating-1), and heating was performed at 130°C under reduced pressure for 1 hour (first heating-2). Furthermore, the powder obtained by the first heating was heated at 250°C in an argon atmosphere for 1 hour (second heating-1), and further heated at 430°C in a nitrogen atmosphere for 8 hours (second heating-2) to obtain a powder.

[0285] The X-ray diffraction spectra of the powder obtained by heating at 130°C, 250°C and 430°C in Example 10 are shown in FIG. Figure 4 .

[0286] (Comparative Example 1)

[0287] In the glove box under nitrogen atmosphere, use mortar that 0.2590g lithium sulfide, 0.4177g phosphorus pentasulfide and 0.1808g elemental sulfur are mixed, are imported into 100 milliliters of reaction tanks (reaction tank 1) together with stirrer.Similarly, weigh 0.1776g lithium iodide, are imported into 100 milliliters of reaction tanks (reaction tank 2) different from above-mentioned together with stirrer.Under nitrogen atmosphere, in reaction tank 1, add the mixed solvent (the total content of ethanol and tetrahydrofuran (THF) in all solvents is 50.1 volume %) of 32.62mL ethanol (EtOH), tetrahydrofuran (THF) and acetonitrile (ACN), stir with magnetic stirring device for 10 minutes and mix.Then, in reaction tank 2, add the solution of reaction tank 1, further stir with magnetic stirring device for 10 minutes and mix.

[0288] Then, using a vacuum pump and an oil bath, heating was performed under reduced pressure at room temperature (20°C) for 1 hour (first heating-1), and heating was performed under reduced pressure at 130°C for 1 hour (first heating-2). Furthermore, the powder obtained by the first heating was heated under reduced pressure at 170°C for 2 hours (second heating-1) to obtain a powder.

[0289] The X-ray diffraction spectra of the powder obtained by heating at 130° C. and 170° C. in Comparative Example 1 are shown in FIG. Figure 5 .

[0290] [Table 1]

[0291] Table 1

[0292]

[0293] *1. Raw material supply methods A to C are as follows.

[0294] A: Mix lithium sulfide, phosphorus pentasulfide, elemental sulfur, lithium bromide and lithium iodide at the same time.

[0295] B: After mixing lithium sulfide, phosphorus pentasulfide and elemental sulfur, mix lithium chloride and lithium bromide.

[0296] C: Mix lithium sulfide, phosphorus pentasulfide and elemental sulfur, and then mix with lithium iodide.

[0297] according to Figures 1 to 3 and Figure 6 , 7As a result, the powders obtained by heating at 200°C in Examples 1 to 9 and the powders obtained by heating at 130°C in Examples 1 to 9 had peaks at 2θ=20.3° and 23.9°, and thus it was confirmed that they were crystalline sulfide solid electrolytes having a sulfide crystalline lithium superion conductor region II type crystal structure. In addition, the ion conductivities of the powders obtained in these Examples were 0.8 to 1.7 mS / cm, respectively, and it was also confirmed that high conductivity could be obtained.

[0298] according to Figure 4 As a result, the powder obtained by heating at 250°C and 430°C in Example 10 had peaks at 2θ=15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°, and thus it was confirmed that it was a crystalline sulfide solid electrolyte having an argyrodite-type crystal structure. In addition, the ion conductivity was 5.0 mS / cm, and it was also confirmed that a high conductivity could be obtained.

[0299] according to Figure 5 As a result, the powder obtained in Comparative Example 1 did not observe peaks derived from the type II crystal structure in the sulfide crystalline lithium superion conductor region at 2θ=20.3° and 23.9°, but peaks believed to be derived from Li7P2S8I or Li4PS4I were observed at 2θ=20.8° and 27.9°. In addition, a peak due to lithium sulfide was also confirmed at 2θ=27.0°, indicating that the reaction did not proceed efficiently.

[0300] Industrial Applicability

[0301] According to the method for producing a sulfide solid electrolyte of the present embodiment, a sulfide solid electrolyte having improved ion conductivity can be efficiently provided. The sulfide solid electrolyte obtained by the production method of the present embodiment is suitable for use in batteries, particularly batteries used in information-related devices or communication devices such as personal computers, cameras, and mobile phones.

Claims

1. A method for producing a sulfide solid electrolyte, characterized in that: include: Mixing a raw material containing a plurality of raw materials in a solvent, wherein the raw materials contain at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms; as well as Then heating, The solvent comprises an organic solvent of an ether solvent and an alcohol solvent in an amount of 60% by volume or more based on the total amount of the solvent. The raw material contains elemental sulfur and lithium sulfide.

2. The method for producing a sulfide solid electrolyte according to claim 1, wherein: The solvent is an ether solvent and an alcohol solvent.

3. The method for producing a sulfide solid electrolyte according to claim 1 or 2, wherein: The solvent includes an alcohol solvent, and the amount of the alcohol solvent used is 0.030 mol or more and 5.0 mol or less relative to 1.0 mol of the lithium sulfide.

4. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 3, wherein: The content of the ether solvent based on the total amount of the solvent is 50.0 volume % or more.

5. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 4, characterized in that: The halogen atom is at least one atom selected from a chlorine atom, a bromine atom, and an iodine atom.

6. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 5, wherein: The heating is performed at a heating temperature of 20° C. to 500° C.

7. The method for producing a sulfide solid electrolyte according to claim 6, wherein: The heating is performed at a heating temperature of 20° C. to 300° C. both inclusive.

8. The method for producing a sulfide solid electrolyte according to claim 7, wherein: The heating is performed by first heating at a heating temperature of 20° C. or higher and lower than 150° C. and second heating at a heating temperature of 150° C. or higher and 300° C. or lower.

9. The method for producing a sulfide solid electrolyte according to claim 6, wherein: The heating is performed at a heating temperature of 200° C. to 500° C.

10. The method for producing a sulfide solid electrolyte according to claim 9, wherein: The heating is performed by heating at a heating temperature of 200° C. or higher and lower than 350° C. or heating at a heating temperature of 350° C. or higher and 500° C. or lower.

11. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 10, wherein: A crystalline sulfide solid electrolyte having a sulfide crystalline lithium superion conductor region type II crystal structure or a crystalline sulfide solid electrolyte having an argyrodite type crystal structure is manufactured.

Citation Information

Patent Citations

  • Solid sulfide electrolyte material, solid-state lithium battery, and method for manufacturing solid sulfide electrolyte material

    JP2013016423A

  • Liquid solution for formation of a solid electrolyte-containing layer of all-solid type lithium secondary battery, all-solid type lithium secondary battery, and method for manufacturing the same

    JP2014191899A

  • Production method of solid electrolyte

    WO2014192309A1

  • Solid lithium electrolytes and process of production

    WO2018054709A1

  • Method for producing solid electrolyte, and electrolyte precursor

    WO2020105737A1